BIODIESEL FROM LOW GRADE USED FRYING OIL USING ESTERIFICATION TRANSESTERIFICATION PROCESS - Hasibuan, Sawarni; Ma’ruf, Amar; Sahirman, Sahirman (Makara Journal of Science, 2009)
Biodiesel from Low Grade Used Frying Oil Using Esterification Transesterification Process. The aim of this research was to obtain the optimal condition for the production of biodiesel from low grade used frying oil through the esterification transesterification process. The experiment was arranged in Completely Randomized Design with Duncan’s advanced test. Results showed that the biodiesel FFA content is ranged between 0.167 to 0.795% (P